Appendicularians and copepods from Scotia Bay (Laurie island, South Orkney, Antarctica): fluctuations in community structure and diversity in two contrasting, consecutive summers - Spinelli, Mariela Lorena (2018)
Coastal Antarctic waters involve habitats of high primary and secondary production with a remarkable sensitivity to environmental changes on different spatio-temporal scales. The current study is the first comprehensive approach to the spatial distribution and the fluctuations in abundance, biomass, community structure, and diversity of the mesozooplankton from different habitats located in Scotia Bay in summers: 2014 and 2015, characterized by a different timing in seasonal sea ice retreat. Mean seawater temperature and abundances of calanoids, cyclopoids, nauplii, and appendicularians were one order of magnitude higher in summer 2014. Despite these environmental differences, biomass values of these groups proved similar for both summers. A total of ten species of copepods and one of appendicularians (Fritillaria borealis) were identified. Oithonid copepods—O. similis, followed by O. frigida—represented the bulk of mesozooplankton abundances in both summers. The highest total mesozooplankton abundance (2111 ind m−3) and biomass (14075 µg C m−3) were found next to an Adélie penguin breeding area (2014), while the highest Shannon index values were found next to a glacier in both summers. Multivariate analyses based on species abundance showed two main groups of sites, one of them encompassing all summer 2014 samplings and the other comprising all summer 2015 samplings. The positive correlation between O. similis and the 2–10 μm Chl-a fraction suggests that summer 2014 represented optimal conditions—in terms of food—for the growth and development of this species. Experimental studies based on natural prey assemblages revealed that O. similis feeds on flagellates rather than on diatoms.